Outbreak investigation of acute watery diarrhea in a village of North India: timely action saved lives - Abu Bashar, Md.; Soundappan, Kathirvel (The Journal of Infection in Developing Countries, 2022)
Introduction: Outbreaks of acute watery diarrhoea are common in developing countries having poor access to safe drinking water and sanitation. An outbreak of acute watery diarrhoea in a village in North India was investigated with the aim to initiate and recommend necessary actions to control it. Methodology: A house to house survey using a specially designed case record form was conducted covering all the households. Stool samples of some of the affected individuals and twenty water samples during and after the outbreak from various sites were collected for laboratory analysis. Results: Out of 624 inhabitants surveyed, 118 were found to be suffering from acute watery diarrhoea (Overall attack rate of 18.9%) with two suspected deaths following diarrhoea. Males and females were affected equally and the age group of 15–44 years was affected predominantly. A peculiar epidemic curve with single peak was noted. One of the stool samples collected during the outbreak grew Vibrio Cholera O1(Ogawa) and twelve out of the twenty water samples including the samples from both the tube wells had high coliform counts indicating fecal contamination. Chlorine levels in all the water samples were found to be inadequate. Conclusions: Local cultural practices such as indiscriminate defecation in public places, using tullu pumps to extract water from the public supply line, poor engineering design and maintenance of the water supply system having leakages at many sites along with inadequate chlorination of the supply water from the tube wells were the risk factors that could have contributed to this outbreak.